Rambutan (Nephelium lappaceum) fats - Mirghani, Mohamed Elwathig Saeed (Springer Cham, 2019)
Rambutan (Nephelium lappaceum) fruit is rich in carbohydrates, lipids, phosphorus, vitamin C, niacin, iron, calcium, copper, protein and fiber. Rambutan seed kernel fat (RSKF) can be a promising alternative edible fat that has the potential to be used in the food industry, especially to replace hydrogenated fat. The main fatty acids in RSKF are arachidic acid (38.3%) and oleic acid (37.1%). These two fatty acids covered 75.7% of the total fatty acids. RSKF exhibited several nutritional, biological and health promoting effects. This chapter reports on the chemical composition and health promoting impacts of RSKF.